The conserved and high K-to-Na ratio in sunflower pollen: Possible implications for bee health and plant-bee interactions - Filipiak, Michał; Shields, Morgan W.; Cairns, Sarah M.; Grainger, Megan N. C.; Wratten, Stephen D. (Frontiers in Plant Science, 2022)
Sodium (Na) concentrations are low in plant tissues, and its metabolic function in plants is minor; however, Na is a key nutrient for plant consumers. Previous studies have thus far focused on Na concentration. Nevertheless, a balanced potassium (K) to Na ratio (K:Na) is more important than Na concentration alone since food with high K:Na has detrimental effects on consumers irrespective of Na concentration. Therefore, plants may actively regulate K:Na in their tissues and products, shaping plant-insect interactions. Studies considering nutritional aspects of plant-insect interactions have focused on nonreproductive tissues and nectar. In this study, we consider pollen as serving a primary reproductive function for plants as well as a food of pollinivores. Plants might regulate K:Na in pollen to affect their interactions with pollinivorous pollinators. To investigate whether such a mechanism exists, we manipulated Na concentrations in soil and measured the proportion of K, Na, and 13 other nutrient elements in the pollen of two sunflower (Helianthus annuus) cultivars. This approach allowed us to account for the overall nutritional quality of pollen by investigating the proportions of many elements that could correlate with the concentrations of K and Na. Of the elements studied, only the concentrations of Na and K were highly correlated. Pollen K:Na was high in both cultivars irrespective of Na fertilization, and it remained high regardless of pollen Na concentration. Interestingly, pollen K:Na did not decrease as pollen increased the Na concentration. We hypothesize that high K:Na in pollen might benefit plant fertilization and embryonic development; therefore, a tradeoff might occur between producing low K:Na pollen as a reward for pollinators and high K:Na pollen to optimize the plant fertilization process. This is the first study to provide data on pollen K:Na regulation by plants. Our findings broaden the understanding of plant-bee interactions and provide a foundation for a better understanding of the role of the soil-plant-pollen-pollinator pathway in nutrient cycling in ecosystems. Specifically, unexplored costs and tradeoffs related to balancing the K:Na by plants and pollinivores might play a role in past and current shaping of pollination ecology.